2019
DOI: 10.1177/1933719118765985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metformin on IVF Outcomes in Overweight and Obese Women With Polycystic Ovary Syndrome: A Randomized Double-Blind Controlled Trial

Abstract: Short-term administration of metformin to overweight or obese women with PCOS undergoing IVF decreased number of the retrieved oocytes but did not improve the LBR. Synopsis Metformin use could decrease the number of retrieved oocytes in overweight and obese women with polycystic ovary syndrome undergoing IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“… 14 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 After full-text assessment, 1 article was excluded because participants did not meet the inclusion criteria, 1 article was excluded because it did not have a parallel control and had incomplete outcomes, and 1 article was excluded because it did not report findings in English (eTable 3 in the Supplement ). Finally, 12 RCTs 14 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 were included in the meta-analysis. In total, 1123 women with PCOS were randomized, with 564 (50.2%) to metformin and 559 (49.8%) to control.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 14 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 After full-text assessment, 1 article was excluded because participants did not meet the inclusion criteria, 1 article was excluded because it did not have a parallel control and had incomplete outcomes, and 1 article was excluded because it did not report findings in English (eTable 3 in the Supplement ). Finally, 12 RCTs 14 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 were included in the meta-analysis. In total, 1123 women with PCOS were randomized, with 564 (50.2%) to metformin and 559 (49.8%) to control.…”
Section: Resultsmentioning
confidence: 99%
“…Main characteristics and specific interventions of included studies are presented in eTable 1 and eTable 2 in the Supplement . Eight studies 14 , 16 , 22 , 24 , 25 , 26 , 28 , 31 reported the full outcomes (ie, OHSS rate, clinical pregnancy rate, and live birth rate). One study 30 did not report OHSS incidence; 1 study 29 did not report clinical pregnancy rates; and 4 studies 23 , 27 , 29 , 30 did not report live birth rates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations